2019
DOI: 10.1016/j.amjoto.2018.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Tone-in-noise detection deficits in elderly patients with clinically normal hearing

Abstract: Purpose: One of the most common complaints among the elderly is the inability to understand speech in noisey environments. In many cases, these deficits are due to age-related hearing loss; however, some of the elderly that have difficulty hearing in noise have clinically normal pure-tone thresholds. While speech in noise testing is informative, it fails to identify specific frequencies responsible for the speech processing deficit. Auditory neuropathy patients and animal models of hidden hearing loss suggest … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 41 publications
(48 reference statements)
2
22
0
Order By: Relevance
“…Sudden SNHL is more common in the early stages (within two years from diagnosis), while progressive SNHL in late stages (after five years) [16][17][18][19][20] or derive from central nervous system demyelination, especially in cases in which no auditory alterations are evident 18,40 .…”
Section: Hearing Loss and Tinnitusmentioning
confidence: 99%
See 1 more Smart Citation
“…Sudden SNHL is more common in the early stages (within two years from diagnosis), while progressive SNHL in late stages (after five years) [16][17][18][19][20] or derive from central nervous system demyelination, especially in cases in which no auditory alterations are evident 18,40 .…”
Section: Hearing Loss and Tinnitusmentioning
confidence: 99%
“…Audiological investigations as tonal and speech audiometry, Auditory Brainstem Responses (ABR), and transient (TEOAE) or Distortion Product Otoacoustic Emissions (DPOAE) are crucial to correctly describe and characterize hearing deficits in patients with MS. Often, clinical audiometry is not able to detect deficits in MS patients possibly due to forms of hidden hearing loss 30,31,40 , and ABR is necessary 16 . A recent review of the literature that included 47 studies and 1533 patients evaluated, among other tests, the role of ABR in MS patients, showing that it was abnormal in the majority of MS patients during the active phase and remained altered in nearly ¼ of the patients even after complete hearing recovery occurred 16 .…”
Section: Hearing Loss and Tinnitusmentioning
confidence: 99%
“…Although these low-spontaneous rate (SR) fibers do not contribute to threshold detection in quiet situations, they contribute to coding of transient stimuli in the presence of continuous background noise [11], leading to the new concept called hidden hearing loss. Therefore, tone in noise detection may be a useful measure in detecting age-related hearing deficits for those patients who express difficulty, but have relatively normal thresholds in quiet [12].…”
Section: Introductionmentioning
confidence: 99%
“…Tone in-noise thresholds may provide frequency specific information in auditory neuropathy patients with normal pure tone threshold. Ralli et al 29 found that, despite having normal hearing (thresholds ≤ 25 dB HL), the Old patients had significantly worse tone in-noise thresholds than the Young patients thus concluding the significance of tone in-noise detection as a effective way for diagnosis of hidden hearing loss. 28 We observed TEOAE and DPOAE result as REFER in 37.5% and 43.8% of patients of tinnitus with normal hearing respectively.…”
Section: Discussionmentioning
confidence: 99%